Inflation Stabilization, Fiscal Deficits and Public Debt Management in Poland - Sweder van Wijnbergen; Nina Budina (Tinbergen Institute, 1999)
Poland edged towards hyperinflation towards the latter half of 1989,but inflation fell dramatically after drastic reformswere enacted in January of 1990. We analyse the consistency betweenfiscal deficits and inflation targets and assessPoland's domestic and foreign debt management policies and the impactof the Brady debt reduction agreement on therelationship between fiscal deficits and inflation. We also assessthe impact of financial sector measures on seignioragerevenue and the sustainability of the low inflation strategy. Suchpolicies are shown to have a direct impact on thesustainability of inflation targets.
Keywords: E63; F34; E52; E41; 330; Fiscal deficits; Public debt; Money demand; Seigniorage; Inflationsbekämpfung; Haushaltsdefizit; Inflation; Inflationssteuerung; Öffentliche Schulden; Schuldenerlass; Schuldenmanagement; Polen